Sistem Pengelolaan Pendidikan di MA Raudatul Muta’allimin Opo-Opo Krejengan Probolinggo Tahun 2021 - Arobi, Ibnu; Komar, Abdul (BAHTSUNA: Jurnal Penelitian Pendidikan Islam, 2022)
Abstract The school as an educational management institution is the second institution after the family which consists of several elements, including the principal, teachers, employees, students and errand boys or school managers. So it is necessary to have an established management and organization so that educational activities run smoothly and are in accordance with the goals of national education. Therefore, to find out in detail about the school management of the Tarbiyah faculty, Zainul Hasan Genggong Islamic University held a teaching practice program. Where this teaching practice is a program that provides material and practice on how to teach well, master classes, interact with students and train students mentally so that they are not awkward when they become real teachers. School management is an integrated part of Teaching Practice activities in schools in the form of an introduction to various aspects of schooling and its management mechanisms, both concerning educational and administrative aspects, under the guidance and coordination of the school principal. Keywords: educational Management, concerning educational and administrative aspects